Unpacking the influence of flight booking website to e-loyalty: empirical evidence from South East Asian Millennials - Susilo,Donny (2020)
Abstract This study aims to understand how Southeast Asian Millennials become loyal to a flight booking website, using the results of an online survey and a E-loyalty model, and structural equation modeling. The findings show that good utilitarian features of website can significantly increase brand equity and positive online experience (flow) of website users while good hedonic features of website can significantly increase positive online experience and trust of website users. Brand equity, positive online experience and trust have a direct and significant effect on e-loyalty. When the brand equity of website, positive online experience and trust of website users are higher, the e-loyalty of millennial customers towards the website is higher. The effect of utilitarian features on trust and hedonic features on brand equity are found to be insignificant. Nevertheless, all the other hypotheses are accepted. This study has successfully expanded Bilgihan’s E-loyalty model application to a different product (flight booking websites) and geographical location (Southeast Asia), proving its generalizability.